PENERAPAN MODEL PEMBELAJARAN EXAMPLE dan NON- EXAMPLE UNTUK MENINGKATKAN AKTIVITAS BELAJAR SEJARAH - DWI ASMAYANTI; Trisnaningsih Trisnaningsih; Edy Purnomo (Jurnal Studi Sosial / Journal of Social Studies, 2016)
This research was a classrom action research. Tools of data collection using observation sheet learning activities with seven indicators of success, namely: 1) Pay attention to the teacher's explanations 2) Asking questions to the teacher 3) Asking questions to other groups during the discussion 4) Answer the teacher's question 5) Reply/responded to the questions from other students during the discussion 6 ) Contribute in the explanation of the task group 7) Contributions of the students when the teacher gives lessons and conclusions at the end of the test results in the form of learning as much as 5 about the essay. Data from the observation and formative tests at each cycle to be ground or material improvement in the next cycle. The results showed that: there is increased activity of learning and cognitive learning outcomes of students in each cycle after the use of models in learning Example and Non-Example subjects of History. Penelitian ini adalah penelitian tindakan kelas. Alat pengumpulan data menggunakan lembar pengamatan aktivitas belajar dengan tujuh indikator keberhasilan yaitu: 1) Memperhatikan penjelasan guru 2) Mengajukan pertanyaan pada guru 3) Menunjukkan pertanyaan pada kelompok lain saat diskusi 4) Menjawab pertanyaan guru 5) Menjawab/menanggapi pertanyaan siswa lain saat diskusi 6) Memberikan kontribusi dalam penjelasan tugas kelompok 7) Kontribusi siswa pada saat guru memberikan kesimpulan diakhir pelajaran dan tes hasil belajar yang berupa soal esai sebanyak 5 soal. Data dari hasil observasi dan tes formatif pada setiap siklus menjadi dasar atau bahan perbaikan pada siklus berikutnya. Hasil penelitian menunjukkan bahwa: terdapat peningkatan aktivitas belajar dan hasil belajar kognitif siswa pada setiap siklus setelah penggunaan model dalam pembelajaran Example dan Non-Examplemata pelajaran Sejarah.Kata kunci : Aktivitas belajar, Sejarah, Example dan Non-Example.